1882-1883 Ga. Laws 48 - (:unkn) unknown (My University, 1883)
Prohibited the concealed carrying of any "pistol, dirk, sword in a cane, spear, Bowie-knife, or any other kind of knives manufactured and sold for the purpose of offense and defense."
Keywords: CARRY - CONCEALED